KOMUNIKASI INTERPERSONAL PEMIJAT PEREMPUAN KELILING DI YOGYAKARTA - Roem, Elva Ronaning; Sarmiati, Sarmiati; Elian, Novi; Diego, Diego; Havifi, Ilham; Tifanny, Nazlya; Vanisya, Winda (Departemen Ilmu Komunikasi Universitas Andalas, 2024)
The profession of mobile female masseuses has unique dynamics, particularly in their interactions with clients. Effective interpersonal communication plays a key role in building trust and comfort, which are crucial for the sustainability of their profession. This study employs a phenomenological approach to explore the subjective experiences of mobile female masseuses in Yogyakarta, focusing on their communication strategies and the reasons behind choosing this profession. Data were collected through in-depth interviews and observations. The findings reveal that they use empathetic verbal and non-verbal communication strategies to establish positive relationships with clients despite facing social stigma and physical demands. In conclusion, adaptive and empathetic communication helps them overcome challenges while ensuring the continuity of their work.